IPRs for agricultural biotechnological inventions : a case of Malaysia : patent and plant variety rights for agricultural biotechnology - Ismail, Suzi Fadhilah (LAP LAMBERT Academic Publishing GmbH & Co. KG, 2011)
This book focuses on the current legal protection for agricultural biotechnological inventions in Europe, the U.S. and Malaysia. It has been a subject of debate whether plants and agricultural biotechnological inventions which includes plants, transgenic plants and plant varieties, can be the subject of patent protection, in addition to or as an alternative to the protection afforded by plant variety rights. Biotechnological patents have been criticized for granting an excessive scope of protection to proprietors, whereas plant variety rights have been slighted for not providing enough protection. The book incorporates the deliberation on the current system as practised in Malaysia, the interface between the patent regime and plant variety rights over agricultural biotechnological inventions as there are possible overlaps between the two systems, notwithstanding the exclusivity of protection of plant varieties under the plant variety right system. The author looks at the prospect for Malaysia as a developing country to enhance its current IPRs framework and legislation in order to develop its agricultural biotechnology industry.